Penggunaan Media Pembelajaran Berbasis Canva Dalam Upaya Meningkatkan Minat Belajar Informatika Materi Algoritma Dan Pemrograman Pada Siswa Kelas X Di SMAN 1 Pekanbaru - Dewi Fatimahwati; Finanta Okmayura; Ahmad Khaidir (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Learning using media based on the Canva application has the advantage that the learning material is made more interesting. As support for direct learning, the use of the Canva application which has a variety of saved file formats, according to Rahmatullahet al (2020), the use of Canva-based audio visual learning media can improve students' informatics learning outcomes. There are also research results from Vivi et al (2021) which state that using the Canva application can help students fulfill online learning assignments at school. According to Yanti in Assidiqi (2020), learning using Canva-based learning media can help students understand learning even though they are at home because there are obstacles in the form of not having textbooks. This is known from the lack of student data recapitulation of the low learning outcomes of students who reach the KKM, namely 14 students out of a total of 38 students in class X.9